Interferon-γ enhances the efficacy of autogenous bone grafts by inhibiting postoperative bone resorption in rat calvarial defects. Issue 3 (July 2016) - Li, Peiqi; Honda, Yoshitomo; Arima, Yoshiyuki; Yasui, Kenichirou; Inami, Kaoru; Nishiura, Aki; Hashimoto, Yoshiya; Matsumoto, Naoyuki
Abstract: Purpose: Interferon (IFN)-γ is a major cytokine produced by immune cells that plays diverse roles in modulating both the immune system and bone metabolism, but its role in autogenous bone grafting remains unknown. Here, we present that local IFN-γ administration improved the efficacy of autogenous bone graft treatment in an experimental rat model. Methods: An autogenous bone graft model was prepared with critically sized rat calvariae defects. Four weeks (w) after bone graft implantation, rats were treated locally with IFN-γ or were not treated. The effect of IFN-γ on bone formation was evaluated for up to 8 w with micro-computed tomography, quantitative histomorphometry, and Von Kossa staining. Osteoclastogenesis was assessed by tartrate-resistant acid phosphatase staining. Immunohistochemistry staining or quantitative polymerase chain reactions were used to estimate the expression of osteoclast differentiation factor and inflammatory cytokines including tumor necrosis factor (TNF)-α, a well-known stimulant of osteoclastogenesis and an inhibitor of osteoblast activity, in defects. Results: Newly formed bone gradually replaced the autogenous bone grafts within 4 w, although severe bone resorption with osteoclastogenesis and TNF-α expression occurred after 6 w in the absence of IFN-γ administration. IFN-γ administration markedly attenuated bone loss, osteoclastogenesis, and TNF-α expression, while it enhanced bone formation at 8 w. Conclusion: Local IFN-γ administration promoted bone formation in autogenous bone grafts possibly via regulating osteoclastogenesis and TNF-α expression. The data provide insights into the potential roles of IFN-γ in autogenous bone grafting.